EXPRESSIONS OF DISAGREEMENT IN ENGLISH BY INDONESIAN LEARNERS OF ENGLISH AND AUSTRALIAN LEARNERS - Elya Aprilia Ramadhani (Universitas Gadjah Mada, 2012)
This research entitled “Expressions of Disagreement in English by Indonesian learners of English and Australian learners” intends to study and compare the similarity and difference between Indonesians and native speakers of English in expressing disagreements. This research also examines the choice of semantic formulae that both groups used toward different interlocutors influenced by familiarity, status and age. To collect data, questionnaires in the form of DCT (Discourse Completion Task) are used. This research involves 40 respondents consisting of 20 Indonesian students of English Department, 20 Australian students from Indonesian Language and Culture Learning Service (INCULS) program, Faculty of Cultural Sciences, UGM. The data are analyzed by using Beebe’s Classification. Both groups share some similarities and differences in expressing disagreements. Both groups employ a similar set of strategy (semantic formulae) but they differ from each other in the ranks and frequencies of semantic formulae used. There are evidences of mostly semantic formulae used, ranks and frequencies of those in relation to the degree of familiarity, status difference and age difference.